If -3m+5=-22, then you do this math: -22-5= -3m. -22-5=-27, so if you take the negative signs away from -27 and -3m, divide 27 by 3 to get 9, therefore m=9.
If 3m - 7 = 8, then m = 5
3m + 11n = 3
M = 22
9m + 9m + 3m + 3m = 24m
If -3m+5=-22, then you do this math: -22-5= -3m. -22-5=-27, so if you take the negative signs away from -27 and -3m, divide 27 by 3 to get 9, therefore m=9.
3m-5 = 7-21 3m = 7-21+5 3m = -9 m = -3
If 3m - 7 = 8, then m = 5
If: 7+3m = -29 then the value of m is -12
The equation 3m - 3m - 7 = 0, simplifies to -7 = 0 this means that the the solution is no solution, since -7 doesn't equal 0.
m = 7 3m-8=13 3m=21 m=21/3 m=7
Well, 3m + m = 4m so 88 divided by 4= 22 there fore m =22 and 3m = 66
3m + 11n = 3
M = 22
3m + 7 = 5 Subtract 7 from both sides: 3m = -2 Divide both sides by 3: m = -2/3
It is a FALSE statement.
m = -12